PERBANDINGAN PENERAPAN KEBIJAKAN PENDIDIKAN INDONESIA DENGAN FINLANDIA - Faradiba Faradiba; Septina Severina Lumbantobing (Universitas Negeri Medan, 2020)
In the process, educational programs that have been previously planned do not always run as planned, so that there is often a policy to solve the latest problems in order to achieve the goal of achieving equal and quality education in accordance with what is mandated in the law. Indonesia as a developing country is deemed necessary to adopt an education system that has been successfully implemented in other countries. Currently, one of the countries that can be used as a reference in the education sector is Finland. This research uses meta-analysis design. The results of this study there are several aspects that can be implemented from existing educational policies in the country of Finland to Indonesia. With an increase in the quality of education in the country of Indonesia is expected to be able to give birth to future generations who can compete internationally.Keywords: Education Policy, Finland, Quality of Education